Distance education and continuing teacher Education: o olhar de Professores da educação profissional - Ferrari Junior, José; Rink, Juliana (Revista Hipótese, 2020)
This research aimed to discuss the view of teachers working in the Professional Technical Education of two State Technical Schools in the interior of São Paulo, about continuing distance education. Document analysis and field research were conducted with 13 teachers through structured questionnaires. The time factor was the main obstacle mentioned, followed by the impersonal character and the prejudice about courses in distance education. The main advantages indicated were flexibility and time management. We hope this article will contribute to the improvement of continuing education for the sport and foster new studies.